I'll build a stairway to paradise : a life of Bunny Mellon - Griswold, Mac K. (Farrar, Straus and Giroux, 2022)
"The story of Bunny Mellon, the great landscape architect and interior designer, becomes a revelatory exploration of extreme wealth in the American century"--